FTY720 (S)-Phosphonate Preserves S1PR1 Expression and Exhibits Superior Barrier Protection to FTY720 in Acute Lung Injury - Wang, Lichun (2014)
OBJECTIVE: Effective therapies are needed to reverse the increased vascular permeability that characterizes acute inflammatory diseases such as acute lung injury (ALI). FTY720 is a pharmaceutical analog of the potent barrier-enhancing phospholipid, sphingosine 1-phosphate (S1P). Because both FTY720 and S1P have properties that may limit their usefulness in patients with ALI, alternative compounds are needed for therapeutic use. The objective of this study is to characterize the effects of FTY720 (S)-phosphonate (Tys), a novel analog of FTY720-phosphate, on parameters of pulmonary vascular permeability in vitro and alveolar-capillary permeability in vivo. SETTING: University-affiliated research institute. SUBJECTS: Cultured human pulmonary endothelial cells (EC); C57BL/6 mice. INTERVENTIONS: EC were stimulated with S1P receptor 1 (S1PR1) agonists to determine effects on S1PR1 expression. ALI was induced in C57BL/6 mice with bleomycin to assess effects of S1PR1 agonists. MEASUREMENTS AND MAIN RESULTS: Tys potently increases human pulmonary EC barrier function in vitro as measured by transendothelial electrical resistance (TER). Reduction of S1P receptor 1 (S1PR1) with siRNA significantly attenuates this TER elevation. Tys maintains endothelial S1PR1 protein expression in contrast to >50% reduction after incubation with S1P, FTY720, or other S1PR1 agonists. Tys does not induce β-arrestin recruitment, S1PR1 ubiquitination, and proteosomal degradation that occur after other agonists. Intraperitoneal administration of Tys every other day for 1 week in normal or bleomycin-injured mice maintains significantly higher lung S1PR1 expression compared with FTY720. FTY720 fails to protect against bleomycin-induced ALI in mice, while Tys significantly decreases lung leak and inflammation. CONCLUSION: FTY720 (S)-phosphonate is a promising barrier-promoting agent that effectively maintains S1PR1 levels and improves outcomes in the bleomycin model of ALI.